Credibility of Central Bank Independence Revisited - Valila, Timo (IMF Working Papers; Working Paper ;, 1999)
The specific role of central bank independence in determining the overall credibility of monetary policy is addressed in this paper. It is argued that the credibility of delegating monetary policy to an independent central bank is endogenous to the credibility of the inflation target because a 'conservative' inflation target may not be compatible with the fiscal policy stance. Also, lack of transparency in designing the institutional set-up is shown to be welfare-reducing.